Effects of positive vs negative forces on the burnout-commitment-turnover relationship. Issue 3 (10th June 2014) - Chen, Ching-Fu; Yu, Ting
Abstract : Purpose: – The purpose of this paper is to examine relationships among job demands, job resources, burnout, organizational commitment, and staff turnover intentions in a volunteer workforce setting. Design/methodology/approach: – To test empirically the positive and negative forces on the burnout – commitment – turnover relationship, this study uses 190 questionnaires collected from museum volunteers who also hold paid service jobs. The data were analysed using structural equation modelling. Findings: – Consistent with previous studies, both job demands and job resources have significant impacts on burnout. Job resources have positive significant impact on organizational commitment. Both burnout and organizational commitment have significant impacts on volunteers' turnover intentions. Research limitations/implications: – An integrated understanding would require different theoretical approaches to volunteering in various settings to determine cross-influences. Moderator analyses might clarify the predictability of job demands and resources. A multilevel research design would provide further insights. Practical implications: – To retain their volunteer workforce, firms should grant volunteers sufficient autonomy and allow them to determine their work processes, which not only reduces burnout but also satisfies psychological control needs. Constructive feedback from colleagues offers better organizational support to volunteers. Originality/value: – This study identifies and empirically tests key indicators of job demands and job resources for volunteers who also hold paid jobs. It helps explain inconsistent reports of the burnout – organizational commitment link by raising the possibility that it is context specific rather than generic.